POLA ASUH ORANGTUA DAN KECENDERUNGAN DELINKUENSI PADA REMAJA - Garvin Garvin (Universitas Bunda Mulia, 2017)
Adolescents undergo drastic changes in terms of physical, cognitive, emotional, and psychosexual aspects. Those changes result in unstable emotions within themselves. Accompanied with high level of curiosity as a process of searching for identity, this emotional instability causes adolescents to frequently engage in actions that do not comply with the rules and norms of the society, known as juvenile delinquency. This stud aims at discovering whether permissive, authoritative, and authoritarian parenting styles are related to juvenile delinquency tendency. The participants of this study are 151 students from X school. This study can be considered as a quantitative research with correlational non-experimental design. Due to abnormal data distribution, Spearman correlation test was used to analyze the data. This study concluded that authoritarian and permissive parenting styles are not related to juvenile delinquency tendency (p>0.05) whereas authoritative parenting style is significantly related to juvenile delinquency tendency (p<0.05). Furthermore, the direction of the relationship between authoritative parenting style and juvenile delinquency tendency revealed negative correlation, which means the more authoritative the parenting style is, the lower the tendency will be. Keywords: Juvenile delinquency, authoritative parenting style, authoritarian parenting style, permissive parenting style